Effect of longitudinal magnetic field on the excess conductivity of monodomain YBa₂Cu₃O₇-δ single crystals - Tiutierieva, K.V.; Zavgorodnya, N.M.; Dovgopolova, Ya.V.; Chernovol-Tkachenko, O.O.; Vovk, R.V.; Chroneos, A. (Functional Materials, 2016)
In the present study influence of longitudinal magnetic field on temperature dependence of the excess conductivity in the temperature interval of transition to the superconducting state in untwinned YBa₂Cu₃O₇-δ single crystals with optimal oxygen content are investigated. Causes of low-temperature tails (paracoherent transitions) in resistive transitions in the superconducting state are analyzed in the framework of implementation of various regimes of the phase state of vortex matter.